Phthalate exposure alters gut microbiota composition and IgM vaccine response in human newborns. (October 2019) - Yang, Yung-Ning; Yang, Yu-Chen S.H.; Lin, I-Hsuan; Chen, Ying-Yu; Lin, Hung-Yun; Wu, Chien-Yi; Su, Yu-Tsun; Yang, Yao-Jong; Yang, San-Nan; Suen, Jau-Ling
Abstract: Postnatal exposure to di-(2-ethylhexyl) phthalate (DEHP), a common plasticizer, is associated with allergy development in childhood, suggesting that DEHP exposure may dysregulate immune response in infants. We investigated whether DEHP exposure in newborns through medical treatment affected the gut microbiota pattern and vaccine response, which are both related to immune development. In this prospective cohort study from May 1, 2016 through July 31, 2017, newborns with respiratory distress who were given intravenous infusions (IVs) were enrolled as the DEHP group, and newborns who did not receive IVs were enrolled as the control group. We excluded patients with perinatal maternal probiotics, vaginal delivery, antibiotic treatment, and exclusive human milk or formula feeding. Of 118 infants, urinary phthalate metabolite analysis revealed that the calculated DEHP concentrations of the newborns treated with IVs (n = 15) were higher than those in the control group (n = 10) (p = 0.0001). DEHP exposure altered bacterial communities both in composition and diversity, particularly decreases in Rothia sp. and Bifidobacterium longum in the DEHP group. Furthermore, DEHP exposure significantly enhanced anti-HBsAg-IgM responses in the DEHP group (p = 0.013). Early-life DEHP exposure alter gut microbiota of newborns and may change their immune responses in later life. Highlights: Newborns expose to di-(2-ethylhexyl) phthalate (DEHP) through medical treatment. Intravenous DEHP exposure to newborns results in transient gut microbial dysbiosis. Newborns exposed to intravenous DEHP develop aberrant IgM response against HBV vaccine.